Analysis of Patient Satisfaction in the Inpatient Unit at Permata Dalima Hospital, Serpong: Analisis Kepuasan Pasien Pada Pada Unit Rawat Inap Di RS Permata Dalima Serpong - Noviane Indah Susanti; Nur Asniati Djaali; Ajeng Tias Endarti (Universitas Mohammad Husni Thamrin, 2026)
Patient satisfaction is an important indicator in assessing the quality of hospital services because it reflects the extent to which patient expectations are met. The increase in the number of National Health Insurance (JKN) participants, which will reach 98.19% by 2024, poses a challenge for hospitals, including Permata Dalima Hospital, in maintaining service quality. The results of the Public Satisfaction Index (IKM) survey show a decline in the score to 85,51%, still below the ideal standard of ≥95%. This is primarily due to complaints from BPJS patients regarding long waiting times, administrative complexity, and limited facilities. This situation indicates differences in service experiences between patient groups based on the financing system and demographic characteristics such as age, education, and occupation. This study aims to determine the relationship between financing type and patient satisfaction after controlling for patient demographics in the Inpatient Unit at Permata Dalima Hospital, Serpong. This study is a quantitative study using a correlational design. The study involved 246 patients receiving services at the Inpatient Unit of Permata Dalima Hospital, Serpong. Unvariate, bivariate, and multivariate analysis methods were used. The bivariate analysis, using the Chi Square test, yielded a p-value of 0.000 (0.000 <0.05), indicating a relationship between the type of financing and patient satisfaction at the Inpatient Unit of Permata Dalima Hospital, Serpong. The multivariate test showed that the p-value for the type of financing (p-value 0.000 and OR of 4.422) and the variable age (p-value 0.211 and OR of 1.423) indicated that age was a Confounding variable in the relationship between the type of financing and patient satisfaction. Permata Dalima Serpong Hospital needs to improve its overall service quality through regular evaluations, strengthening the competency of healthcare workers, and ensuring equal service quality for all patients, both BPJS and Non BPJS, to achieve optimal and sustainable satisfaction levels.